The Internationalization of Emerging Market Firms: A Context-Specific Study - Tamara Stucchi (Copenhagen Business School (CBS), 2013)
This Ph.D. dissertation investigates some International Business (IB) issues, which emerge from a specific context of research. The study takes inspiration from one of the most currently debated phenomena in IB literature, i.e. the internationalization of Emerging Market (EM) firms. The recent global emergence of these firms is substantial and particularly interesting under several points of view, especially because the IB literature has traditionally been dominated by western-centric theories, whose applicability to the case of EM firms might be questionable. The present Ph.D. thesis recommends an approach to the study of the internationalization of EM firms that can contribute to the advancement of IB literature in general. This is illustrated by the four research articles of the thesis, where a single-country EM context is used to draw general implications useful for researchers, practitioners and policy makers. More in details, the first paper “Emerging market firms' acquisitions in advanced markets: Matching strategy with resource-, institution- and industry-based antecedents” studies the antecedents that can affect the motivations for the acquisitions that EM firms undertake in advanced markets. The second article, entitled “Time to internationalization and evolving institutions: An event history analysis of Indian firms”, analyzes domestic firms' earlier versus later internationalization, during a period of radical institutional changes. The third paper, “The role of Overseas National Ownership in Outward FDI: A study of the Indian diaspora”, studies how the presence of overseas national shareholders can influence homeland firms' outward FDI. Finally, the last article is entitled "Business groups' internationalization: The role of the domestic geographical scope" and analyzes one possible explanation for business groups' internationalization, from an organizational learning perspective. The Ph.D. thesis is empirically based on a very comprehensive sample of Indian firms. The data are collected from different sources, i.e. the Prowess database, the Zephyr database, the Indian Census and the World Competitiveness Yearbook. The potential value of this singlecountry context perspective is highlighted throughout the Ph.D. thesis, and clearly emerges while I address the different issues of the four research articles.
hdl:10398/8699
Keywords: 650